Pengaruh Bauran Pemasaran Terhadap Keputusan Konsumen Berbelanja Pada PT Jumbo Swalayan Manado - Sendow, Glady Ester; Pio, Riane Johnly (JURNAL ILMU ADMINISTRASI (JIA), 2013)
Abstract. This study aimed to determine the effect of marketing mix on consumer shopping decisions on PT Jumbo Supermarket in Manado. Marketing mix consists of product, price, promotion and place as the independent variable and the consumer's decision to shop as the dependent variable. In this research using correlation and regression analyzes with the total sample of 45 customers. Partial results showed all the hypotheses of the elements of the marketing mix significantly influence the consumer's decision to shop, but the biggest influence is the element of the place. Likewise, simultaneous marketing mix significantly influence consumer shopping decisions. Impikasi of this study, expected jumbo self-management should continue to integrate the elements of the marketing mix to enable the powerful synergy for maximum business performance. For further research, researchers can develop other variables that consumer shopping decisions can be assessed from different elements. Keywords: Marketing Mix, Consumer Shopping Decisions